The role of imaging in head and neck cancer: An overview of different imaging modalities in primary diagnosis and staging of the disease - Vishwanath, Veena; Jafarieh, Sarah; Rembielak, Agata (Journal of Contemporary Brachytherapy, 2020)
Radiology has an essential role in diagnosis, staging, and management in all subspecialties related to oncology. It has a broad utility from its use as an initial screening tool for cancer detection, followed by staging and surveillance of disease as well as the delivery of appropriate treatment regimens. In order to plan a treatment, the use of different modalities of radiological imaging are a key factor for pre-treatment planning and staging of the extent of disease in accordance with tumor-node-metastasis (TNM) system for highly conformal treatments, such as brachytherapy (BT). In this work, we present an overview of main modalities of imaging and principles of their application especially in head and neck cancer, with its diagnosis, treatment, follow-up with post-treatment changes, and overall management.